Features of cues and processes during chloroplast-mediated retrograde signaling in the alga Chlamydomonas. (July 2018) - Rea, Giuseppina; Antonacci, Amina; Lambreva, Maya D.; Mattoo, Autar K.
Highlights: Imbalance of chloroplast homeostasis triggers the synthesis of signaling molecules that transmit information to the nucleus. Photosynthesis controls retrograde responses through ROS and ROS-generated signals, tetrapyrroles, and Ca 2+ ions. Gene expression, post-transcriptional and post-translational processes are remodeled to recover a functional state. Chlamydomonas is suitable for decoding retrograde signaling in ways unlike plants with multiple chloroplasts. Abstract: Retrograde signaling is an intracellular communication process defined by cues generated in chloroplast and mitochondria which traverse membranes to their destination in the nucleus in order to regulate nuclear gene expression and protein synthesis. The coding and decoding of such organellar message(s) involve gene medleys and metabolic components about which more is known in higher plants than the unicellular organisms such as algae. Chlamydomonas reinhardtii is an oxygenic microalgal model for genetic and physiological studies. It harbors a single chloroplast and is amenable for generating mutants. The focus of this review is on studies that delineate retrograde signaling in Chlamydomonas vis a vis higher plants. Thus, communication networks between chloroplast and nucleus involving photosynthesis- and ROS-generated signals, functional tetrapyrrole biosynthesis intermediates, and Ca 2+ -signaling that modulate nuclear gene expression in this alga are discussed. Conceptually, different signaling components converge to regulate either the same or functionally-overlapping gene products.